Analisis Hubungan Aliran Dana Investor Asing terhadap Perilaku "Herding" di Saham-saham LQ45 Bursa Efek Indonesia (BEI) - , Iis Haryono ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research was conducted to examine the relationship of foreign investment flows into Indonesia's capital market with the herding behavior of domestic investors. Swift flow of foreign funds into the capital market has increased the capitalization of transactionin the stock market. This prompted the formation of a belief among investors that when follow the movement of the foreign funds in the capital market, investors could get abnormal return. This research using purposive sampling method in order to minimize bias in the results obtained. The research takes a sample of stocks that have never been out of the LQ45 index membership during the period February 1, 2010 until January 31, 2012. From these criteria gained a total of 32 stocks meet the criteria of 61 stocks that have become members of the LQ45 index over the period. The testing conducted on four portfolios with members drawn at random from the 32 stocks that meet the foregoing criteria. Testing performed using the method of chisquare test to compare the herding of the four beta portfolio and the flow of foreign funds into the portfolio. The results showed that there was no correlation between the flows of foreign investment into Indonesia's capital market with domestic herding investor behavior in a portfolio. The flow of foreign funds into the capital market Indonesia is making a positive impact on the movement of stock price index (Securities and Exchange Commission, 2008), but does not provide a significant impact on a portfolio herding behavior.